VII CONGRESS WITH INTERNATIONAL PARTICIPATION «DEVELOPMENT OF PHARMACOECONOMICS AND PHARMACOEPIDEMIOLOGY IN RUSSIAN FEDERATION» (IRBIS LLC, 2015)
VII Congress with International Participation «Development of Pharmacoeconomics and Pharmacoepidemiology in Russian Federation»